INNOVATIVE TECHNOLOGIES IN LEARNING AND TEACHING FOREIGN LANGUAGES (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This passage gives an overview of importance of modern approach in acquiring language skills. Their effectiveness, teaching methods and scientists’ ideas are given in this article as supportive examples.